FORMULASI SALEP EKSTRAK ETANOL DAUN NANGKA (Artocarpus heterophyllus Lam.) dan UJI EFEKTIVITAS TERHADAP PENYEMBUHAN LUKA TERBUKA PADA KELINCI - Hamzah, Hamdiyah; Fatimawali, Fatimawali; Yamlean, Paulina V. Y.; Mongi, Jeane (PHARMACON, 2013)
ABSTRACT Jackfruit leaves is a plant that work as medicine on healing process of skin diseases, especially in wounds. The purpose of this study is to determine the quality of ointment from ethanolic extract of Jackfruit leaves at the concentration on 5%, 10% and 15% and the effect of the open wound healing in rabbits. Type of this research is laboratory experimental. In this research maceration was done as the extraction method to got the extract of Jackfruit leaves. The ointment of ethanolic extract from jackfruit leaves made within 3 concentrations of 5%, 10% and 15%. On the testing ointment using organoleptic test, homogenity test and pH test. The effectiveness assay to heal the open wounds using 5 groups, Betadine ointment (positive control), basic ointment (negative control), the ointment of ethanolic extract from Jackfruit leaves 5%, 10%, and 15% of the 3 rabbits with a 1.5 cm was done and observed until 7 days. The data were processed statistically using One Way ANOVA (Analysis Of Variant) and followed by LSD (Least Significant Different). Results of this study showed that the ointment of ethanolic extract from Jackfruit leaves on the concentration of 5%, 10% and 15% produce qualified ointment of organoleptic test, homogenity test and pH test, also give the effect of open wound healing in rabbits and the most effective cure is the ointment of ethanolic extract from Jackfruit leaves 15%. Keywords: ethanolic extract of Jackfruit leaves, ointment, wound, rabbit.